"A writer's diary" of F.M. Dostoevsky in the Russian and German reception. On the problem definition - Lilenko I. Yu. Irina; Litvintseva A. I. Anastasiya; Malikov A. V. Alexey; Prokopenko V. O. Valentin (Филологические науки, 2017)
Title screen